The complete mitochondrial genome of the Megalobrama skolkovii (Cyprinidae: Cultrinae). (2nd January 2016) - Yang, Huaqiang; Li, Qiang; Shu, Hu; Yang, Lidong; Wu, Xiaorui; Yue, Lei; Hou, Liping
Abstract: The complete mitochondrial DNA (mtDNA) sequence of Megalobrama skolkovii was first presented in this study. The mitochondrial genome is 16, 620 bp in length, including 13 protein-coding genes, 2 ribosomal RNA gens (12S rRNA and 16S rRNA), 22 transfer RNA genes (tRNA) and a control region (D-loop), with the gene identical to that of typical vertebrates. The overall base composition of the light strand are 31.23% A, 24.73% T, 16.16% G and 27.88% C. Two copies of tandem repeat sequence was found in the control region.